Pluralisme Hukum Sumber Daya Alam dalam Tata Kelola Penyadapan Getah Pinus pada Lokasi Perhutanan Sosial di Kabupaten Lima Puluh Kota: Pluralism of Natural Resources Law in The Management of Pine Sap Tapping at Social Forestry Location in Lima Puluh Kota Regency - Maryanti Lestari, Tesya; Yonariza, Yonariza; Rizaldi, Rizaldi (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Pine trees were planted in 1976 as reforestation plantations on customary land by the government. After the issuance of the Forest Use Agreement in 1982, some of the forest was included in state forests. In 2011, the district government began using pine resin as a source of regional revenue by issuing pine resin extraction permits. In 2017, several pine forests became part of the Social Forestry work area, forest management permits were issued by the Ministry of Environment and Forestry to the Nagari Forest Management Institution. The study aims to identify the rights and obligations that arise, and analyze the interaction between state law and customary law in the governance of pine resin tapping. The research methodology used is qualitative with a multi-case study approach. The results of the study are that the management of pine resin tapping involves various actors. The rights and obligations that arise include the rights and obligations of: the Nagari Forest Management Institution, workers, investors, and ninik mamak (traditional landowners). The interaction between state law and customary law in the governance of pine resin tapping occurs through three legal subsystems: substance, structure, and legal culture. Legal pluralism in the management of pine resin tapping results in overlapping policies, necessitating integration between customary and state law to achieve more sustainable and equitable management. These findings underscore the importance of more harmonized policies to address legal complexity and serve as a basis for future strategic steps in natural resource governance. Keywords: Pine resin tapping, state law, customary law, legal pluralism, Nagari Forest